КАРАКАЛПАКСТАН В 1980-Е ГОДЫ - Кощанов, Б.; Юсупов, К. (SCIENCE and SOCIETY, 2022)
The article deals with a decline in the water level in the Amu Darya and in the Aral Sea, a decrease and deterioration in the quality of drinking water, a decrease in the average wage of farmers , desertification of the bottom of the Aral Sea and the “cotton case” in Uzbekistan and Karakalpakstan.